Kansas Pride Review - Kahl, Dan; Hoch, Connie; Smerchek, Ruth; Stinson, Jeanne (My University, 2005)
Summary of the 2005 actiivities of the Kansas PRIDE program and affiliated communities.
Keywords: Administrative and Research Reports; Community Development